Penentuan Rute Terpendek Jalur Distribusi Air Artesis Menggunakan Kruskal - Wulandari, Diah Ayu Retnani; Arifin, Fajrin Nurman (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Water flow distribution to home residents from the artesian well is affected by infrastructure. The more houses that distributed makes decreased amount supply of artesian water in every house. the longer of pipe leight and many branches traversed makes decrease of water supply because there will be many possible pipeline leaks. The more pipes used make the more expensive infrastructure cost. This problem occurs in Jubung area. These problems is one variation of the minimum Spanning Tree problems. This problem can be solved by the shortest path optimization route. It uses network method by implementing graph theory through kruskal algorithm. The first step is determined the nodes and sides. Nodes represent house and the sides represents the connecting pipes between houses. Kruskal is chosen because the kruskal focuses on the side and the graph is incomplete. focus of this study is the length optimation of the connecting pipe that is represented by side. In the pipe infrastructure figure map is representing of an incomplete graph because there are several nodes that are not connected to all nodes because it is adapted to the contour of the land that is not possible traversed the pipe. The results is there are several paths that are changed, especially the side to connect between node 1-4, 4-12, 19-20, 21-6 dispensed because forming cycles. The result of this research is kruskal can make decreasing infrastrukture cost Rp.7.535.500 with length of 201,5 meter so can save Rp.4.401.000 from Rp Rp.11.936.500.